2019
DOI: 10.21851/obr.43.02.201906.130
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observation of immediately-installed implants after extraction: Retrospective clinical study

Abstract: The aim of this study was to compare and analyze the survival rate, success rate, and loss of marginal bone of internal and external hexes and presence or absence of microthreads of implant immediately installed after tooth extraction. Forty-four implants were installed in 30 patients, average follow-up period was 80 months, and each product was divided into 3 groups. Group 1 is Osstem TS III implant, Group 2 is Osstem US II implant, and Group 3 is Implantium implant. Panoramic and periapical radiographs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Elkhaweldi et al reported that the survival rate of RBM surfacetreated implants was 95.2%, but the survival rate of SLA surface-treated implants was higher than 99.1% [10]. Using this SLA surface treatment method, Osstem (Busan, Korea) developed implants with SA surfaces that were subjected to sandblasting and acid etching using alumina, but more long-term observational studies on the implants are necessary [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Elkhaweldi et al reported that the survival rate of RBM surfacetreated implants was 95.2%, but the survival rate of SLA surface-treated implants was higher than 99.1% [10]. Using this SLA surface treatment method, Osstem (Busan, Korea) developed implants with SA surfaces that were subjected to sandblasting and acid etching using alumina, but more long-term observational studies on the implants are necessary [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the stability of the implant was excellent, with no cases of failed implants in delayed placement after bone grafting and a healing period. implants with SLA surfaces has been shown in several studies [3][4][5][6][7][8]. SA implants (Osstem Implant, Busan, Korea) were developed using SLA method, sandblasting and acid-etching using alumina.…”
mentioning
confidence: 99%